The effectiveness of the complex application of humates and micronutrient fertilizers on the Macleaya x kevensis Turill. and Macleaya cordata (Willd.) R.Br. - O. A. Bykova; R. N. Thaganov; V. R. Thaganov; A. I. Morosov (Овощи России, 2023)
Relevance. In the arsenal of agents with antibacterial activity, a significant place belongs to preparations based on the raw materials of two types of Macleia - Macleaya x kevensis Turill. and Macleaya cordata (Willd.) R.Br. used both in medical and veterinary practice. It is possible to provide the domestic pharmaceutical industry with these medicinal raw materials in full through the development of methods for increasing yields and adapting Maclea to unstable environmental weather conditions.Material and methods. Experiments to study the effect of the use of humates and microfertilizers on these indicators were laid in the fields of the North Caucasus branch of VILAR in 2019-2021. We studied the morphological and economically valuable traits of two species of Maclea, evaluated the growth rates of plants, the yield of raw materials, the content of alkaloids and their collection per hectare under optimal and dry weather conditions.Results. Differences between the two types of Maclea are established in terms of morphological and economically valuable traits. Maclea heart-shaped palmate-lobed leaves are light green in color, the roots are vertical, round-cylindrical, reaching a depth of 50 cm or more, plant height is 300-350 cm. at a depth of 25-30 cm, plant height 200-250 cm. % versus 0.162-0.164% for the heart-shaped Maclea. The dependence of the growth, development and productivity of two types of Maclea on meteorological conditions has been established. Under the conditions of insufficient water supply and high temperatures, the loss of yield in the first year of vegetation in Macleaya cordata is 14%, in the second year - 6%, in Macleaya x kevensis - 21 and 12%, respectively. Foliar treatments with the Normat L complex with Ferovit in the first year of vegetation contributed to a decrease in crop losses and an increase in the yield of alkaloids per 1 hectare in both types of makley, in the second year, with these treatments, an increase in yield by 7-11% was observed, the collection of alkaloids per hectare increased by 14- 18%.